Israel : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Israel focuses on the fiscal institutions and the political economy in Israel. The paper addresses two questions. First, is there evidence for political-economy distortions to Israel's fiscal policy? Second, what institutional changes could help in limiting these distortions? The paper presents some data on Israel's political system and an empirical analysis of the relation between fiscal policy and the political infrastructure. It also presents some options for reducing political economy distortions through reforms in the budget process and institutions.